Eating Pattern and Eating Behavior during Covid-19 Pandemic: Survey on Adults who Work from Home - Lucky Ade Sessiani; Dwi Hartanti (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2022)
Covid-19 pandemic impacts many changes in daily life, either in health, social, economic, and psychological context. People will be most likely to change the way they live their life every day, including in eating and working. This research aims to describe empirically how was the eating pattern and eating behavior on adults who work from home (WFH) during Covid-19 pandemic. Instruments used in this research were The Eating Pattern Questionnaire and The Eating Behavior Questionnaire, adapted from The Adult Eating Behavior Questionnaire (He, Jinbo, et.al., 2019). Total of 338 respondents (age mean = 35,13 years old; 69.8% female) from various professional backgrounds across Indonesia had completed the questionnaires. Results based on descriptive statistical analysis implied most of respondents had experience changes in eating pattern while WFH, such as: more food consumption, increased snack time, less consumption of fruit and vegetables, and less physical exercise. Changes in eating behavior, namely: 1) enjoy meal time more; 2) more excited to try new variants of food; 3) feel more uncomfortable for delayed meal-time; 4) get hungry more easily; and 5) think more about food when not busy. This research sets the foundation for regulation or intervention strategy in healthy eating behavior as a notable indicator for either nutritional and mental health status.